Goods 2 interior products from sketch to use - Willems, Marlous; Martins, Ana (Amsterdam Frame Publishers, 2016)
In 'Goods 2', iconic and contemporary interior design products are analysed and featured from conceptual design sketch to realisation. Whether crafted by the hands of a carpenter, made by glassblowers in the Bavarian forest or rolling off a belt in a high-tech production facility, every product has a story to tell -- which continues until it ends its journey within a contemporary interior. Focuses on all interior product ranges -- from chairs to tables, from floor lamps to down lights, and from kitchens to bathrooms. Each product is showcased on 8 pages. These pages include contact details and profiles of the producer and the designer, product photos, drawings, sketches, renderings, photos of the design and manufacturing process, and photos of interior projects in which the product has been used. Frame editors select leading design producers and their associated designers; then the designer and Frame editor decide together which product will be featured.
Bathroom -- Floor and wall covering -- Lighting -- Seating -- Storage -- Tables and office units.
Includes indexes.
Prof. Jocelyn C. Pinzon (Recommending faculty) - Bookfair2017
Keywords: Interior decoration; House furnishings; Design and technology